Distribution of life in the Philippines - Dickerson, Roy E.; Merrill, Elmer D.; McGregor, Richard C.; Schultze, W.; Taylor, Edward H.; Herre, Albert W.C.T. (Manila, Philippines Bureau of Printing, 1928)
Monograph of the Bureau of Science; 21
Keywords: Zoology; Botany; Natural history